Structure, agency and local climate governance: how do individual actors exploit local contexts to shape policymaking in smaller cities and towns? - Wolfgang Haupt; Leonie Laug; Peter Eckersley (Regional Studies, 2025)
Previous studies stress that structural conditions influence local climate action, but often neglect the role of agency in policymaking. Drawing on fieldwork in 11 German towns, we show how municipal managers frame climate-related policies in different ways to gain local support for action. Although these framings are influenced by each town's socio-economic, demographic and political conditions, as well as its vulnerability to climate threats, they nonetheless highlight the importance of individuals in policymaking. We then present a two-dimensional framework to inform future research into structure and agency in local governance, whilst cautioning that undertaking such studies can be difficult.
Keywords: 300